2021
DOI: 10.3390/toxins13060378
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Uses of Bacterial Subunit Toxins

Abstract: The B subunit pentamer verotoxin (VT aka Shiga toxin-Stx) binding to its cellular glycosphingolipid (GSL) receptor, globotriaosyl ceramide (Gb3) mediates internalization and the subsequent receptor mediated retrograde intracellular traffic of the AB5 subunit holotoxin to the endoplasmic reticulum. Subunit separation and cytosolic A subunit transit via the ER retrotranslocon as a misfolded protein mimic, then inhibits protein synthesis to kill cells, which can cause hemolytic uremic syndrome clinically. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 235 publications
(297 reference statements)
0
28
0
Order By: Relevance
“…Stx is a classic representative of the AB 5 toxins composed of a single A subunit (StxA, 32 kDa), where "A" stands for "activity", and five identical B subunits (StxB, 7.7 kDa each), where "B" stands for "binding" [4,20,164] as shown in Figure 1A,B. The catalytic A subunit of the ribosome-inactivating protein exerts interruption of the protein biosynthesis at the ribosomes and the pentameric B subunit binds to globo-series GSLs on the target cell surface [70,[165][166][167]. Stxs are grouped in the two types Stx1 and Stx2, which are further subdivided into three Stx1 and (at least until now) nine Stx2 subtypes (for correct nomenclature refer to Scheutz and collaborators) [50].…”
Section: Shiga Toxin Structurementioning
confidence: 99%
“…Stx is a classic representative of the AB 5 toxins composed of a single A subunit (StxA, 32 kDa), where "A" stands for "activity", and five identical B subunits (StxB, 7.7 kDa each), where "B" stands for "binding" [4,20,164] as shown in Figure 1A,B. The catalytic A subunit of the ribosome-inactivating protein exerts interruption of the protein biosynthesis at the ribosomes and the pentameric B subunit binds to globo-series GSLs on the target cell surface [70,[165][166][167]. Stxs are grouped in the two types Stx1 and Stx2, which are further subdivided into three Stx1 and (at least until now) nine Stx2 subtypes (for correct nomenclature refer to Scheutz and collaborators) [50].…”
Section: Shiga Toxin Structurementioning
confidence: 99%
“…It is noteworthy that he was also the first physician to propose the therapeutic use of the botulinum toxin. In 1897, after an epidemic of botulism in the city of Elezel (Belgium) due to the consumption of ham of homemade pork, the microbiologist Emile van Ermengem, discovered the bacterium and concluded that the disease was caused by the anaerobic growth of the microorganism and that the endospores produced a toxin [11]. In the 1920s, scientists were able to isolate one of the seven toxins produced by Clostridium, such as the toxin BoNT-A, which is now the active form of the commercial drug Botox™.…”
Section: Timeline Of Historical Events About Bonts Discoverymentioning
confidence: 99%
“…In the 1920s, scientists were able to isolate one of the seven toxins produced by Clostridium, such as the toxin BoNT-A, which is now the active form of the commercial drug Botox™. During the Second World War, the research on the manufacture of biological weapons that could infect and affect the nervous system had a strong impulse, so two military laboratories, one in the United States and one in England, studied the effects of toxin B [11,12].…”
Section: Timeline Of Historical Events About Bonts Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…After binding and cellular uptake, these toxins transport their toxic cargo to the cytosol through multiple trafficking pathways, the most common of which involve retrograde transport through the endoplasmic reticulum or endocytic trafficking from early to late endosomes followed by pH-dependent endosomal escape. Already, a number of modular toxins have been exploited for their ability to deliver heterologous cargo molecules to the cytosol, including fluorescent proteins ( 1 ), epitope tags ( 2 ), nanobodies ( 3 , 4 ), various recombinant enzymes ( 5 , 6 , 7 , 8 , 9 , 10 ), and nucleic-acid-binding proteins ( 11 , 12 , 13 ). Bacterial toxin-inspired drug delivery (BTIDD) platforms, such as those described for the cytotoxic necrotizing factor (CNF) toxins ( 14 ) that assemble from modular components, could be expanded to noncognate therapeutic cargos if the determinants for efficient cytosolic delivery of the biologic cargo were more fully understood.…”
mentioning
confidence: 99%